Verbs of Lexical and Semantic Field «Agricultural Production (Crop Production)» in the Ukrainian Language: Identification Criteria and Typology (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article studies the Ukrainian verbs which denominate agricultural production processes, in particular soil cultivation, planting crops and looking after them, harvesting etc. Semantic peculiarities of the above verbs are tracked, their identification criteria are traced. The typology of these verbs is also examined.
Keywords: verb; lexical and semantic field; typology of the verbs